Influences on antibiotic prescribing by non-medical prescribers for respiratory tract infections: a systematic review using the theoretical domains framework. (7th August 2020) - Chater, Angel; Family, Hannah; Lim, Rosemary; Courtenay, Molly
Abstract: Background: The need to conserve antibiotic efficacy, through the management of respiratory tract infections (RTIs) without recourse to antibiotics, is a global priority. A key target for interventions is the antibiotic prescribing behaviour of healthcare professionals including non-medical prescribers (NMPs: nurses, pharmacists, paramedics, physiotherapists) who manage these infections. Objectives: To identify what evidence exists regarding the influences on NMPs' antimicrobial prescribing behaviour and analyse the operationalization of the identified drivers of behaviour using the Theoretical Domains Framework (TDF). Methods: The search strategy was applied across six electronic bibliographic databases (eligibility criteria included: original studies; written in English and published before July 2019; non-medical prescribers as participants; and looked at influences on prescribing patterns of antibiotics for RTIs). Study characteristics, influences on appropriate antibiotic prescribing and intervention content to enhance appropriate antibiotic prescribing were independently extracted and mapped to the TDF. Results: The search retrieved 490 original articles. Eight papers met the review criteria. Key issues centred around strategies for managing challenges experienced during consultations, managing patient concerns, peer support and wider public awareness of antimicrobial resistance. The two most common TDF domains highlighted as influences on prescribing behaviour, represented in all studies, were social influences and beliefs about consequences. Conclusions: The core domains highlighted as influential to appropriate antibiotic prescribing should be considered when developing future interventions. Focus should be given to overcoming social influences (patients, other clinicians) and reassurance in relation to beliefs about negative consequences (missing something that could lead to a negative outcome).